Why the COVID-19 Pandemic Could Increase the Corporate Saving Trend in the Long Run - Markus Demary; Stefan Hasenclever; Michael Hüther (Intereconomics, 2021)
Given the global trend in corporate saving over the last decades, the COVID-19 crisis raises doubts about the persistence of companies' saving behaviour due to the losses which have occurred in many companies caused by the isolation of households and by lockdowns. Before the pandemic, corporate net lending activities had been increasing for decades due to various factors ranging from the rise in uncertainty after the global financial crisis to the increased reliance on internal funding for research and development expenditures. In Germany, the rise in corporate saving was accompanied by an increase in equity capital and a reduction in the corporate sector's reliance on bank loans. This article argues that the coronavirus crisis is most likely to interrupt the trend in corporate saving in the short run due to the decline in companies' revenues. Nonetheless, similar to the pattern observed in the aftermath of the financial crisis, it seems reasonable to conjecture that the COVID-19 shock will strengthen corporate saving in the long run as companies may attempt to restore their liquidity and equity capital buffers to better prepare for future shocks. This will in turn create downward pressure on real interest rates and complicate the conduct of monetary policy.
Keywords: 330